Clinical implications of genome-wide DNA methylation studies in acute myeloid leukemia. Issue 1 (December 2017) - Li, Yan; Xu, Qingyu; Lv, Na; Wang, Lili; Zhao, Hongmei; Wang, Xiuli; Guo, Jing; Chen, Chongjian; Li, Yonghui; Yu, Li
Abstract Acute myeloid leukemia (AML) is the most common type of acute leukemia in adults. AML is a heterogeneous malignancy characterized by distinct genetic and epigenetic abnormalities. Recent genome-wide DNA methylation studies have highlighted an important role of dysregulated methylation signature in AML from biological and clinical standpoint. In this review, we will outline the recent advances in the methylome study of AML and overview the impacts of DNA methylation on AML diagnosis, treatment, and prognosis.